2020
DOI: 10.1080/10717544.2020.1850921
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic block polymer-based self-assembly of high payload nanoparticles for efficient combinatorial chemo-photodynamic therapy

Abstract: (2020) Amphiphilic block polymerbased self-assembly of high payload nanoparticles for efficient combinatorial chemo-photodynamic therapy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…51 , 52 Studies have shown that HCPT and photosensitizer loaded PEG NPs showed excellent anticancer efficiency under laser irradiation. 53 , 54 In addition to light triggering, the development of photosensitizers activated by specific triggers such as enzyme-activated has received much attention. 55 , 56 Lu et al synthesized a cathepsin B-activated photosensitizer, further PEGylated and modified with tumor cell-targeting peptide cRGD and used as a nanocarrier to load HCPT.…”
Section: Organic Npsmentioning
confidence: 99%
“…51 , 52 Studies have shown that HCPT and photosensitizer loaded PEG NPs showed excellent anticancer efficiency under laser irradiation. 53 , 54 In addition to light triggering, the development of photosensitizers activated by specific triggers such as enzyme-activated has received much attention. 55 , 56 Lu et al synthesized a cathepsin B-activated photosensitizer, further PEGylated and modified with tumor cell-targeting peptide cRGD and used as a nanocarrier to load HCPT.…”
Section: Organic Npsmentioning
confidence: 99%
“…In this regard, it has recently been demonstrated that different chemophotodynamic treatments can induce a synergistic cytotoxic effect on HeLa cells [ 41 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12‐20 ] However, simple bolus administration of chemotherapeutics and photodynamic therapeutics cannot achieve sustained synergistic therapeutic effects due to differential pharmacokinetics, biodistribution, and metabolism profiles of the drugs. [ 21 ] Thus, various types of nanoscale drug delivery systems (NDDSs), such as liposomes, [ 22‐23 ] polymeric micelles, [ 24‐30 ] mesoporous silica nanoparticles, [ 31 ] and others, [ 32‐38 ] have been developed for the co‐delivery of chemotherapeutics and photodynamic therapeutics. NDDSs are expected to overcome drug resistance by increased drug solubility, prolonged circulation time, programmed drug release, and sometimes improved cellular uptake.…”
Section: Background and Originality Contentmentioning
confidence: 99%